(untitled) (Al-Academy, 2016)
Many researchers ’ views about class selectors popular theatre in the world, whom he found in political deals popular presentations while others in comedy shows or dealing with social problems, or simply build a direct pattern of relationship between actors and audience were popular, and certainly the Iraqi popular theatre has its own parameters, structural differences result of Iraqi society at all levels, so the researcher found the search problem is to answer the question that (what are category classes Or within the category of Iraqi popular theatrical-in the play of - the string and the bird which un – example ) , then select the aim has his research of detecting those parameters, and search scientific significance as to scholars and researchers. Therefore, the researcher take the historic flight to the evolution of popular theatre globally and regionally in the first section of the theoretical framework and then reviewed the concept of the musical world. And in the procedures of search. The researcher has the optional justifications that sample ( play the string and the bird) and perhaps the most important of his offer of popular and public success yet more than twenty-five years on display and it’s also consistent with the objectives of the research , and then analyzed descriptive analytical, in the main findings based on the theoretical framework indicators and perhaps the most important of these results is that the theatrical show oF theoretical framework which includes all category classes founded in the theatrical world popular